Deploying the Qline System for a QKD Metropolitan Network on the Berlin OpenQKD Testbed - Matheus Sena; Georg Harder; Ronny Doring; Ralf-Peter Braun; Michaela Ritter; Oliver Holschke; Marc Kaplan; Marc Geitz (IEEE Photonics Journal, 2025)
Quantum Key Distribution (QKD) systems have the potential to provide secure communication by offering unconditionally secure key exchange between distant parties. However, the integration of QKD into existing communication networks presents challenges, particularly when it comes to the deployment of trusted nodes and the establishment of secure connections over metropolitan distances. In this study, we present a novel approach to address these issues by introducing a trusted-node-free design on a metropolitan scale for the seamless integration of a QKD system into the Berlin OpenQKD optical fiber testbed. Our innovative design leverages conventional telecom modulators and a standard Wavelength-Division Multiplexing - Arrayed Waveguide Grating (WDM-AWG), offering a practical solution for flexible multi-partner communication and enabling full connectivity between non-adjacent nodes. In this study, we not only observed relatively low QBER ( $< $ 5.5%) but also a rather stable key rate between nodes in the Qline system over approximately 130 hours ( $≈$ 5.4 days) for a lab-based back-to-back setup. Later on, a more complex experimental scheme is integrated into Berlin OpenQKD optical fiber testbed encompassing multiple C-band frequencies (191.75–195.75 THz) and extending over metropolitan distances (up to 39.8 km), providing a foundation for secure quantum communication networks with enhanced scalability and versatility.